Influencia del estrés laboral en el desempeño de los trabajadores de la empresa constructora T&T Arquitectos SAC - Tueros Capurro, Maria Fernanda (2021)
The objective of this research work was to determine the relationship between stress and work performance of the workers of the Company T&T Arquitectos SAC, which was formulated based on the general problem How does work stress influence the performance of the workers of the different areas in a construction company? The research was quantitative and the design used was non-experimental with a cross-sectional and correlational level; The randomly collected sample was of 27 professional workers. For data collection, an ILO-WHO Work Stress Questionnaire was applied to measure work stress and an evaluation of work performance prepared by the company itself. The result obtained showed, through the use of the IBM SPSS Statistics 26 system, that there is no statistically significant correlation between both variables, for which it was concluded that work stress is not a determining factor in the performance of the employees of the company T&T Arquitectos SAC. However, it can be noted that at the sample level there was a positive relationship between better performance and lower level of stress, observed mainly in the administration area. Additionally, the impact of COVID -19 on the performance and stress of workers was investigated, obtaining in general a poor improvement post-pandemic. Finally, as a professional in Administration, it was possible to fulfill the original motivation of the work, generating a source of useful information for the organization both to know the status of its workers, and to identify the critical points that allow it to make decisions in the future.